Buffer zone use by mammals in a Cerrado protected area - Paolino, Roberta Montanheiro; Versiani, Natalia Fraguas; Pasqualotto, Nielson; Rodrigues, Thiago Ferreira; Krepschi, Victor Gasperotto [UNESP]; Chiarello, Adriano Garcia (Revista Biota Neotropica, 2016)
Habitat loss and degradation is threatening mammals worldwide. Therefore, Protected Areas (PA) are of utmost importance to preserve biodiversity. Their effectiveness, however, depends on some management strategies such as buffer zones, which prevent/mitigate the impact of external threats and might increase the amount of available habitat for wildlife existing within reserves. Nevertheless, how intensively terrestrial mammals use buffer zones remains little studied, particularly in the Neotropical region. Aiming to analyse the use of a buffer zone (5 km wide) by medium and large-sized mammals, we modelled the occupancy probabilities of five species of conservation concern including local (interior and buffer zone) as a site covariate, simultaneously controlling for imperfect detection. Data collection was made with camera traps from April to September 2013 in a 9000 ha Cerrado PA (interior'') and in its surrounding area (39721.41 ha; buffer zone''). This PA (Jatai Ecological Station) is immersed in a landscape where sugarcane plantations predominate in the northeastern of the state of Sao Paulo. We also conducted an inventory to compare the number and composition of species between interior and buffer zone. A total of 31 mammal species (26 natives) was recorded via camera traps and active search for sightings, vocalizations, tracks and signs. Occupancy estimates for Myrmecophaga tridactyla, Leopardus pardalis and Pecari tajacu were numerically higher in interior. On the other hand, Chrysocyon brachyurus had the highest occupancy in buffer zone, while the largest predator, Puma concolor, used both areas similarly. However, as the confidence intervals (95%) overlapped, the differences in occupancy probabilities between interior and buffer were weak for all these species. Additionally, regarding only the species recorded by cameras, the observed and estimated richness were similar between interior and buffer zone of the PA. Our data demonstrated that the buffer zone is indeed used by medium and large-sized mammals, including conservation-dependent ones. The lack of enforcement of current legislation regarding buffer zones is therefore a real threat for mammals, even when protection is guaranteed in the interior of protected areas.
Keywords: Medium and large-sized mammals; camera trapping; detection probability; occupancy; Jatai Ecological Station